Tattooed Skin and Health - Serup, Jørgen; Kluger, Nicolas; Bäumler, Wolfgang (Karger, 2015)
With about 10-20% of the adult population in Europe being tattooed, there is a strong demand for publications discussing the various issues related to tattooed skin and health. Until now, only a few scientific studies on tattooing have been published. This book discusses different aspects of the various medical risks associated with tattoos, such as allergic reactions from red tattoos, papulo-nodular reactions from black tattoos as well as technical and psycho-social complications, in addition to bacterial and viral infections. Further sections are dedicated to the composition of tattoo inks, and a case is made for the urgent introduction of national and international regulations. Distinguished authors, all specialists in their particular fields, have contributed to this publication which provides a comprehensive view of the health implications associated with tattooing.